A Framework for Governance Capacity: A Broad Perspective on Steering Efforts in Society. Issue 9 (October 2022) - van Popering-Verkerk, Jitske; Molenveld, Astrid; Duijn, Michael; van Leeuwen, Corniel; van Buuren, Arwin
In the network society, the capacity to deal with societal issues is spread among interacting actors in governance networks. Knowledge about this capacity, often called "governance capacity, " is still fragmented and quite incoherent. The aim of this study is therefore to gain an integrated understanding of governance capacity. To do this, we conducted a literature review and organized focus groups. This resulted in the selection of five elements of governance capacity: (1) collective action, (2) coordination, (3) resilience, (4) learning, and (5) resources. We used these elements to form the first contours of a governance capacity framework.